2021
DOI: 10.3390/plants11010018
|View full text |Cite
|
Sign up to set email alerts
|

Pistachio Nuts (Pistacia vera L.): Production, Nutrients, Bioactives and Novel Health Effects

Abstract: Epidemiological and clinical studies have indicated positive outcomes related to tree nut consumption. Here, we review the production, nutrient, phytochemical composition and emerging research trends on the health benefits of pistachio nuts (Pistacia vera L.). Pistachios are a good source of protein, fiber, monounsaturated fatty acids, minerals and vitamins, as well as carotenoids, phenolic acids, flavonoids and anthocyanins. Polyphenols in pistachios are important contributors to the antioxidant and anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 96 publications
(106 reference statements)
0
36
0
Order By: Relevance
“…The endocarp, which is covered with a fleshy, thin hull that is light green in color with red undertones, is inedible. In comparison to other nuts, pistachios contain a high concentration of compounds that have antioxidant and anti-inflammatory properties [60]. Nuts have positive health effects on a variety of metabolic conditions, including hypercholesterolemia, hyperglycemia, hyperhomocysteinemia, and everything else that goes along with them.…”
Section: Pistachiosmentioning
confidence: 99%
“…The endocarp, which is covered with a fleshy, thin hull that is light green in color with red undertones, is inedible. In comparison to other nuts, pistachios contain a high concentration of compounds that have antioxidant and anti-inflammatory properties [60]. Nuts have positive health effects on a variety of metabolic conditions, including hypercholesterolemia, hyperglycemia, hyperhomocysteinemia, and everything else that goes along with them.…”
Section: Pistachiosmentioning
confidence: 99%
“…Epidemiological and/or clinical trials have shown that nut consumption has a positive influence on health, by reducing the risk of suffering CVD [ 15 , 31 , 32 ], hypertension [ 33 ], T2DM [ 34 ] and obesity [ 35 ], among others. These beneficial effects are a consequence of their unique composition since nuts are nutrient-dense foods with healthy MUFA and PUFA fatty acid composition, dietary fibre, high-quality vegetable protein, vitamins, and minerals, along with carotenoids, phytosterols, and phenolic compounds previously described, with recognized benefits to human health [ 3 , 10 , 11 , 36 ]. Regarding pistachio, there is wide evidence confirming its beneficial health effects and, particularly, its positive contribution to minimizing the risk for CVD [ 10 , 11 ].…”
Section: Health Benefits Of Pistachio Consumptionmentioning
confidence: 99%
“…Syria (2%), Greece (1%), and others, such as Italy, Spain, Greece, Tunisia, Afghanistan, China, and Australia, account for the remaining 1% [ 8 ]. Although pistachio has been the least explored nut, there is broad evidence confirming its beneficial health effects and, particularly, its positive contribution to minimizing the risk for CVD [ 10 , 11 ], among other pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is important to emphasize that as a nutraceutical, the shell of the allis shad offers the benefit of reducing side effects for the patient; compared to some traditional drugs that have been used as nutraceuticals in the treatment of type 2 diabetes, it has the advantage of having fewer side effects on patients than other typical drugs used to treat type 2 diabetes [ 98 ]. Another study by Barreca et al [ 99 ] showed how antioxidants can be extracted from pistachio waste; Only by using organic solvents was it possible to extract about 20 compounds with cytoprotective and antioxidant properties from the ripe pistachio shell [ 100 ]. They are catechin, gallic acid, isoehamnetin-3-O-glucoside, quercetin-3-O-rutinoside and naringin [ 101 ].…”
Section: Nano Formulation Of Bioactive Compoundsmentioning
confidence: 99%